Making welfare resilient – Creating stable & sustainable welfare systems in times of declining economic growth - Katharina Bohnenberger; Martin Fritz (Universität Duisburg-Essen, Institut für Sozioökonomie (ifso), 2020)
Economic growth is no longer a sustainable solution for the challenges faced by the welfare state; here we explain alternatives and how they can align with a Green Deal and the Just Transition: Current welfare systems rely on economic growth to manage the mounting challenges of demographic change, digitalisation and ecological and economic crises. One consequence of this structural dependence on economic growth is that there are often negative social and economic outcomes in times of secular stagnation and recession. Transforming welfare systems so that they flourish without economic growth is a pressing challenge that will have significant implications for the sustainability of our welfare systems and the economic and social resilience of our societies. Research on sustainable welfare identifies four main strategies to reduce the reliance of welfare systems on economic growth, and increase their resilience in an ecologically sustainable way: 1. Invest in preventive social policy, from healthcare and education to urban planning. 2. Promote economic equality through minimum & maximum income caps, time-banking and by shifting the tax base of welfare states towards capital, financial transactions & ecologically-damaging goods. 3. Meet citizens' basic needs through universal basic services and universal basic voucher schemes. 4. Green employment through sectoral shifts, sustainable workers' rights, and climate insurances. The strategies above, which work to reduce the dependence of welfare systems on economic growth, also entail co-benefits like gender-equality, work-life balance, community building, and reductions in material footprint. In what follows, we list concrete steps the EU can take to promote resilient and Sustainable Welfare systems.
Keywords: 330